Regularized nonnegative matrix factorization: Geometrical interpretation and application to spectral unmixing - Zdunek, Rafał (Zielona Góra: Uniwersytet Zielonogórski)
Nonnegative Matrix Factorization (NMF) is an important tool in data spectral analysis. However, when a mixing matrix or sources are not sufficiently sparse, NMF of an observation matrix is not unique. Many numerical optimization algorithms, which assure fast convergence for specific problems, may easily get stuck into unfavorable local minima of an objective function, resulting in very low performance.
Keywords: blind source separation; nonnegative matrix factorization; active-set algorithm; regularized NMF; polytope approximation